MENINGKATKAN KEMAMPUAN BERKOMUNIKASI BAHASA INGGRIS MELALUI AUDIO LINGUAL METHOD PADA SISWA KELAS X AKUNTANSI 1 SMK NEGERI 1 BUNGO: MENINGKATKAN KEMAMPUAN BERKOMUNIKASI BAHASA INGGRIS MELALUI AUDIO LINGUAL METHOD PADA SISWA KELAS X AKUNTANSI 1 SMK NEGERI 1 BUNGO - NURMALA YANTI (Jurnal Tunas Pendidikan, 2020)
This study aims to describe the steps of implementing the ALM (Audio Lingual Method) method in learning English, knowing the parts of the ALM method implementation activities that can make students more interested and active in learning English. The right teaching method will have a positive impact on the learning process, especially in learning English. Is an ALM method in teaching English to class X Accounting 1 students of SMKN 1 Bungo. While the data collection techniques are by means of observation, interview, and documentation. Based on the research results, the teacher uses six techniques from the ALM method in teaching English in the classroom, namely dialogue memorization techniques, backward build up (expansion) drill, and repetition drill in the first observation. While in the second observation, the teacher used the chain drill technique, question and answer drill, and complete the dialogue. The results of the learning process were good with a percentage of 75.86% in cycle 1 and 93.1% in cycle 2. From cycles 1 and 2 there was an increase of 17.24%.